Potential geographic distribution and habitat utilization of Lacerta viridis (Squamata: Lacertidae) in northern Türkiye - Mehmet Kürşat Şahin; Muammer Kurnaz (Journal of Taibah University for Science)
The genus Lacerta, particularly the green lizard (Lacerta viridis), is a significant lizard group in the Western Palearctic. This study aims to predict its geographic range in Northern Türkiye and identify key habitat types based on the CORINE Land Cover classification. Occurrence records, gathered from published sources and on-site investigations, were analyzed using a 30 arc-second resolution layer and bioclimatic parameters from WorldClim v.2.1. The distribution was modeled in kuenm, and habitat use was assessed with generalized linear models. Results show that the green lizard’s occurrence is strongly influenced by precipitation dynamics and it prefers areas with little to no shade. These findings highlight the importance of precipitation in determining the species’ distribution and suggest further research on local dynamics for effective conservation.